Dicionário Bilíngue Kaiwá- Português - Barros, Eliane Berendina Loman de (2014)
Although more than 180 indigenous languages are still spoken in Brazil, the descriptions produced by linguists of these languages in terms of grammar and lexicon, still result in few direct benefits to their indigenous communities. In the southern region of Mato Grosso do Sul State, between Maracaju and the border of Paraguay, there is a large group of Indians, most of them being of Guaraní origin. Among them, the largest group is the Kaiwá people, with a population of 43,400 people, almost all speakers of the Kaiwá language (IBGE 2010), living in more than 30 indigenous communities. Some scientific papers have been produced about the Kaiwá language, such as phonological and morphological descriptions, the last one by Cardoso (2008). However there was no study devoted specifically to the lexicon of this language. Considering this reality, this research has as its objective the lexicographic description of the Kaiwá lexicon, by means of the production of a bilingual Kaiwá-Portuguese dictionary, taken from oral language data collected in two synchronies (1960 and 2013), in order to provide a record, albeit partial, of the universe of Kaiwá language words, for their speakers and for those who want to know the language, especially teachers and students in the school environment as an instrument of aid for education. The work took as its basis the reflections on language (SAUSSURE, 1970; SAPIR, 1969; 1971), the concept of Word (BIDERMAN, 1998a) and basics of Lexicography that guide the production of dictionaries (BIDERMAN, 1978; 1998b; HAENSCH, 1982, among others). The research also considered historical, geographic, socio-economic, cultural and religious data of the Kaiwá people, from authors such as Schaden (1982), Brand (1997) and Vietta (2007), in order to better understand the current condition of the Kaiwá people in the region studied. It also contains a short description of the grammar of the Kaiwá language, especially the section on wordclasses, because this was listed as obligatory information for the dictionary entries. The research methodology consisted mainly in the construction of two corpora formed from two collections of oral texts, in 1960 and 2013, with interviews with 21 Kaiwá indians, from the Indian villages of Dourados and Panambizinho, which generated a total of 65 stories, 26,300 occurrences of words and 3,143 different words. The stories were organized using a linguistic analysis program called Fieldworks Language Explorer (FLEx) and the words were selected and compiled to be lemmatized in the dictionary. The Bilingual Kaiwá-Portuguese Dictionary has a nomenclature of 1,034 entries, arranged alphabetically. The lexicon collected in two synchronies points to changes already solidified and others underway in the Kaiwá language, including the presence of loanwords. In summary, the dictionary produced, despite its incompleteness in terms of nomenclature, represents a first initiative in the systematization of the Kaiwá lexicon in a work lexicographically presented, thus representing an important step in terms of a written record of the documentation and dissemination of the Kaiwá language.